(untitled) - Cahill, Thomas (New York, 2003)
Cahill explores the legacy of the ancient Greeks, from the origins of Greek culture to the birth of Western literature.
Keywords: English language,Ngôn ngữ Anh; Study and teaching,Học và dạy